Chronology and evolution of magmatism in the Urup Island (Kuril Archipelago) from K-Ar isotope datings and diatomic analysis. - Kovtunovich, P Yu; Lebedev, V A; Chernyshev, I V; Arutyunyan, E V (PANGAEA, 2004)
An isotope-geochronological study of Neogene-Quaternary igneous rocks from the Urup Island (Greater Kuril Ridge) was carried out. It was established that magmatic activity in the island developed during the last 10 my and it was not interrupted by long inactive periods. K-Ar data obtained along with results of diatomic analysis are in good agreement with the regional stratigraphic scheme of Paleogene and Neogene deposits and the intraregional correlation scheme of magmatic rocks in the Kuril Islands, which are developed for the State Geologic Map, scale 1:200 000 (Second edition). In the present-day territory of the Urup Island, the earliest Late Miocene - Early Pliocene (10.5-4.5 Ma) magmatic stage was associated with formation of the Rybakovsky andesite volcanic complex, which is represented by an effusive series (Rybakovskaya Suite) and subvolcanic rocks. Actually at the same time (6.6-4.7 Ma), but at a great depth, intrusive bodies of the Prasolovsky plagiogranite-diorite plutonic complex were intruded. The Pliocene stage of magmatism in the Urup Island is characterized by formation of rocks of the Kamuysky dacitic volcanic complex (4.0-2.1 Ma). This complex is locally represented only by subvolcanic acidic bodies, and its occurrence in the island is limited. During the Pliocene - Early Neopleistocene stage of magmatism (3.0-0.8 Ma) the Fregatsky andesibasalt volcanic complex was formed in the Urup Island. This complex includes effusive series (Fregatskaya unit) and subvolcanic bodies. Quaternary time in the Urup Island is characterized by eruptive activity in subaerial conditions with formation of effusive-pyroclastic intermediate-basic rocks of the Bogatyrsky Middle Neopleistocene - Holocene complex (<0.5 Ma). Rocks of this complex formed stratovolcano cones. Pyroclastic rocks of the Rokovsky dacitic volcanic complex were erupted simultaneously. The mentioned magmatic complexes of the Urup Island well correlate with the distinguished magmatic complexes within the bounds of contiguous insular blocks of the Greater Kuril Arc and confirm uniform geologic history of magmatic development of the region.
K-Ar dating of magmatic rocks from the Urup Island, Kuril Island Chain
Keywords: Age, dated; Age, standard deviation; Archive of Ocean Data; ARCOD; Area/locality; Argon-40; Argon-40, standard deviation; Comment; Potassium; Potassium, standard deviation; Rock type; Sample code/label; Urup-120; Urup-121; Urup-132; Urup-137; Urup-140; Urup-147; Urup-152; Urup-1759; Urup-4258; Urup-4261; Urup-5502; Urup-5505; Urup-5513; Urup-5521; Urup-5525; Urup-5531; Urup-5542; Urup-5543; Urup-5545; Urup-5548; Urup-5549; Urup-560; Urup-563; Urup-570; Urup-625; Urup-630; Urup-7005; Urup-7006; Urup-7010; Urup-7013; Urup-7020; Urup-7031; Urup-8073; Urup-8074; Urup-8075; Urup-A-1; Urup-A-10; Urup-A-11; Urup-A-12; Urup-A-13; Urup-A-14; Urup Island